Environmental change and household livelihood strategies: preliminary observations from field work in different locations - David A Preston (Faculty of Geography, Universitas Gadjah Mada, 1986)
The theoretical framework and objectives of a study of environmental change and evolving household livelihood strategies, which will include field work in Central Java, are outlined. Preliminary results of previous, related field work in Luzon (Philippines) and highland Ecuador (South America) are reported. Two changes that seem of importance in both areas so far studied are the increasing importance of commercial farming in central locations (near to village centres) and the decreasing intensity of use of land on the periphery of rural communities. Preliminary observations in Central Java suggest that household livelihood strategies are more diversified than in either case study area in Luzon or Ecuador and that such diversification has increased through time. The relative importance of farming and the use of natural resources does not seem to have diminished.